Anomalous dynamics of melanosomes driven by myosin-V in Xenopus laevis melanophores - Brunstein, Maia (2009)
The organization of the cytoplasm is regulated by molecular motors, which transport organelles and other cargoes along cytoskeleton tracks. In this work, we use single particle tracking to study the in vivo regulation of the transport driven by myosin-V along actin filaments in Xenopus laevis melanophores. Melanophores have pigment organelles or melanosomes, which, in response to hormones, disperse in the cytoplasm or aggregate in the perinuclear region. We followed the motion of melanosomes in cells treated to depolymerize microtubules during aggregation and dispersion, focusing the analysis on the dynamics of these organelles in a time window not explored before to our knowledge. These data could not be explained by previous models that only consider active transport. We proposed a transport-diffusion model in which melanosomes may detach from actin tracks and reattach to nearby filaments to resume the active motion after a given time of diffusion. This model predicts that organelles spend -70% and 10% of the total time in active transport during dispersion and aggregation, respectively. Our results suggest that the transport along actin filaments and the switching from actin to microtubule networks are regulated by changes in the diffusion time between periods of active motion driven by myosin-V. © 2009 by the Biophysical Society.